2022
DOI: 10.2337/db22-0399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GLP-1 and GIP on Islet Function in Glucose-Intolerant, Pancreatic-Insufficient Cystic Fibrosis

Abstract: Impaired insulin and incretin secretion underlie abnormal glucose tolerance (AGT) in pancreatic insufficient cystic fibrosis (PI-CF). Whether the incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) can enhance pancreatic islet function in CF is not known. We studied 32 adults with PI-CF and AGT randomized to receive either GLP-1 (n=16) or GIP (n=16) during glucose-potentiated arginine (GPA) testing of islet function on two occasions with either incretin or p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A total of 89 CF participants and 5 non-CF controls were enrolled in studies that included baseline assessment of both MMTT and GPA during an approximate 10-year period ( 5 , 6 , 10 12 ). Four CF participants and one non-CF control were unable to complete one or both tests and were, therefore, excluded from the present analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 89 CF participants and 5 non-CF controls were enrolled in studies that included baseline assessment of both MMTT and GPA during an approximate 10-year period ( 5 , 6 , 10 12 ). Four CF participants and one non-CF control were unable to complete one or both tests and were, therefore, excluded from the present analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors of dipeptidyl peptidase-4 (DPP-4) prevent inactivation of endogenous GLP-1 and GIP, and our group has shown that treatment of adults with PI-CF and abnormal glucose tolerance with the DPP-4 inhibitor sitagliptin for 6 months improved the rate and degree of postprandial insulin secretion during the MMTT, although did not improve post-prandial glucose tolerance ( 11 ). This favorable effect upon insulin secretion may be attributed to GLP-1 as infusion of GLP-1, but not of GIP, improves glucose-dependent β-cell insulin secretion in PI-CF ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are ongoing studies ( NCT01851694 ) of incretin mimetic agents such as the glucagon‐like peptide‐1 (GLP‐1) agonists or the dipeptidyl peptidase‐4 (dpp‐4) inhibitors, and small studies show GLP‐1 agonists increased insulin secretion in PwCF with glucose intolerance. 168 However, an RCT on the effect of Sitagliptin (a DPP‐IV inhibitor) on islet function in pancreatic insufficient PwCF with abnormal glucose tolerance found no improvement in meal‐related glucose excursion or insulin response. 169 …”
Section: Treatment Of Cfrdmentioning
confidence: 99%